2020
DOI: 10.3758/s13414-020-02206-9
|View full text |Cite
|
Sign up to set email alerts
|

Statistical regularities cause attentional suppression with target-matching distractors

Abstract: Visual search may be disrupted by the presentation of salient, but irrelevant stimuli. To reduce the impact of salient distractors, attention may suppress their processing below baseline level. While there are many studies on the attentional suppression of distractors with features distinct from the target (e.g., a color distractor with a shape target), there is little and inconsistent evidence for attentional suppression with distractors sharing the target feature. In this study, distractor and target were te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…Second, on distractor-absent trials, reaction times (RTs) increased when the target was shown on the high-probability distractor position compared with when it was shown on a low-probability distractor position. The reduced distractor interference on the high-frequency distractor position was attributed to the shielding of visual search from likely distractor positions (e.g., Goschy et al, 2014 ; Sauter et al, 2018 ) or altered distractor filtering (e.g., Ferrante et al, 2018 ), but by far the most frequent interpretation was that it resulted from attentional suppression (Di Caro & Della Libera, 2021 ; Di Caro et al, 2019 ; Kerzel & Huynh Cong, 2021 ; Liesefeld & Müller, 2021 ; Sauter et al, 2021 ; Sauter et al, 2019 ; van Moorselaar et al, 2020 ; van Moorselaar & Slagter, 2019 ; van Moorselaar & Theeuwes, 2021a , 2021b ; Wang & Theeuwes, 2018a , 2018b , 2018c ). Attentional suppression of the high-frequency distractor position was assumed to be learned through the repeated presentation of the distractor on the same position and served to reduce distractor interference.…”
Section: Introductionmentioning
confidence: 99%
“…Second, on distractor-absent trials, reaction times (RTs) increased when the target was shown on the high-probability distractor position compared with when it was shown on a low-probability distractor position. The reduced distractor interference on the high-frequency distractor position was attributed to the shielding of visual search from likely distractor positions (e.g., Goschy et al, 2014 ; Sauter et al, 2018 ) or altered distractor filtering (e.g., Ferrante et al, 2018 ), but by far the most frequent interpretation was that it resulted from attentional suppression (Di Caro & Della Libera, 2021 ; Di Caro et al, 2019 ; Kerzel & Huynh Cong, 2021 ; Liesefeld & Müller, 2021 ; Sauter et al, 2021 ; Sauter et al, 2019 ; van Moorselaar et al, 2020 ; van Moorselaar & Slagter, 2019 ; van Moorselaar & Theeuwes, 2021a , 2021b ; Wang & Theeuwes, 2018a , 2018b , 2018c ). Attentional suppression of the high-frequency distractor position was assumed to be learned through the repeated presentation of the distractor on the same position and served to reduce distractor interference.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, however, these studies used shape targets and colour singletons as salient distractors. It is possible that the dimensional overlap in our study (i.e., colour targets and colour distractors/cues) made it difficult for participants to apply second-order suppression to a dimension that was also relevant to the task (e.g., Pomper et al, 2023 ; Weichselbaum & Ansorge, 2018 ; but see Kerzel & Huynh Cong, 2020 ). Maintaining search templates for features from different dimensions is known to weaken top-down guidance ( Biderman et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%